Determination of the Electrokinetic Mobility of Cell Nuclei in the Bucal Epithelium with Oral Piercing Made from Various Dental Metals - Savelieva Н. М.; Shatov П. О. (Actual Dentistry, 2026)
The electrokinetic mobility of buccal epithelial nuclei is a promising noninvasive method for assessing cell membrane integrity and metabolism. Surface charge indicators reflect differentiation, proliferation, apoptosis, and enzyme activity and enable detection of early homeostatic disorders under the influence of local and systemic factors. The buccal epithelium is accessible and renewable, allowing repeated monitoring without invasive procedures, which is valuable for athletes, children, and patients with chronic mucosal lesions. Purpose of the study. To determine the effect of orofacial piercing material on the electrokinetic mobility of buccal epithelial cell nuclei and the acid-base status of oral fluid, as well as to evaluate the effectiveness of the proposed mouthwash in patients with piercings. Materials and methods. The study included 95 participants: 68 with orofacial piercings (experimental group) and 27 without piercings (control group). The leading group is divided by piercing material: medical steel (316L), gold alloy (14K), titanium (ASTM F-136), and silver (22K). The electrokinetic mobility of buccal epithelial cell nuclei was determined using the Shakbazov method (1986) by electrophoresis of cells obtained from the cheek mucosa in an isotonic NaCl solution. The results were expressed as a percentage of nuclei displaced under the action of an electric field. The acid-base status of oral fluid was measured with a portable ionometer on an empty stomach on days 3, 7, 15, and 30. Patients in the leading group used the rinse once a day for 30 days, after which the pH was re-determined. Statistical processing was performed using Student’s t-test (p < 0.05). Results. Univariate analysis of variance indicated that the piercing material significantly affected the electrical conductivity of buccal epithelial nuclei (ECPN; F > 5, p < 0.001). The lowest value was recorded in patients with piercings in subgroup 1 — 43.17% (p < 0.001); a moderate decrease was observed in subgroups 2 — 62.78% and 3 — 63.34% (p < 0.001), while in subgroup 4 it did not differ from the control group — 71.29% (p > 0.05). The initial pH of the oral fluid was physiological (6.00–6.22) and homogeneous (p > 0.05). In the early days, there was a temporary decrease in pH in subgroups 1 and 3, which partially normalized by day 30 (6.38–6.74). After rinsing, the pH stabilized and gradually increased, particularly in the 2nd and 4th subgroups (+0.4–0.48 units, p < 0.05). The amplitude of pH fluctuations decreased from 0.6–0.8 to 0.3–0.4 units, indicating an improvement in the buffering properties of oral fluid (p < 0.01). Conclusion. Piercing material affects the electrokinetic mobility of buccal epithelial nuclei: medical steel causes a pronounced decrease in ECPY KBE, gold and titanium alloys have a moderate effect, and silver has no effect. The initial pH of oral fluid was physiological, but fluctuations were observed in the first few days, which normalized by the end of the observation period. The use of mouthwash stabilizes the pH and improves the buffering capacity of oral fluids.